Measurement of inclusive jet and dijet production in $pp$ collisions at $\sqrt{s}=7$ TeV using the ATLAS detector - ATLAS collaboration (2997 authors); Aguilar-Saavedra, Juan Antonio; Amaral, Pedro; Anjos, Nuno; Carvalho, João; Castro, Nuno Filipe; Conde Muiño, Patricia; Do Valle Wemans, André; Fiolhais, Miguel; Gomes, Agostinho; Gonçalo, Ricardo; Jorge, Pedro; et al. (My University, 2011)
Inclusive jet and dijet cross sections have been measured in proton-proton collisions at a centre-of-mass energy of 7 TeV using the ATLAS detector at the Large Hadron Collider. The cross sections were measured using jets clustered with the anti-kT algorithm with parameters R=0.4 and R=0.6. These measurements are based on the 2010 data sample, consisting of a total integrated luminosity of 37 inverse picobarns. Inclusive jet double-differential cross sections are presented as a function of jet transverse momentum, in bins of jet rapidity. Dijet double-differential cross sections are studied as a function of the dijet invariant mass, in bins of half the rapidity separation of the two leading jets. The measurements are performed in the jet rapidity range |y|<4.4, covering jet transverse momenta from 20 GeV to 1.5 TeV and dijet invariant masses from 70 GeV to 5 TeV. The data are compared to expectations based on next-to-leading order QCD calculations corrected for non-perturbative effects, as well as to next-to-leading order Monte Carlo predictions. In addition to a test of the theory in a new kinematic regime, the data also provide sensitivity to parton distribution functions in a region where they are currently not well-constrained.